Online Buying and Selling Through Social Media to Increase Efficiency and Fairness Islamic Economic Perspective - Muhammad Samsunar; Rahmawati Muin; Nasrullah Bin Sapa (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2025)
Purpose/Objective This study aims to examine online buying and selling practices conducted through social media platforms and analyze their role in increasing efficiency and fairness from an Islamic economic perspective. Methods This study uses a qualitative descriptive approach based on an extensive literature review of academic journals, books, Islamic jurisprudence (fiqh),muʿāmalāt (Islamic jurisprudence), and regulations related to digital commerce and social media-based transactions. Social media platforms such as Instagram, Facebook, WhatsApp, and TikTok are used as illustrative examples to illustrate contemporary online commerce practices commonly implemented by small and medium-sized enterprises. Results Findings indicate that online transactions via social media can significantly improve economic efficiency by reducing transaction costs, expanding market reach, and accelerating information exchange. From an Islamic economic perspective, these practices are considered permissible (halal) as long as they comply with sharia principles, including transparency (bayān), informed consent, and the ability to communicate effectively. together (tarāḍī), honesty (ṣidq),and avoid ghara ,deception(tadlīs), and Injustice (ẓulm). Unfair practices such as misleading product information, unclear pricing, and non-transparent delivery systems have been identified as violations of Islamic ethical standards and can undermine trust and fairness in digital transactions. Implications This study implies and contribute that strengthening sharia compliance, ethical awareness, and regulatory oversight in social media commerce is crucial to ensure fairness, consumer protection, and sustainable digital economic development in accordance with Islamic economic values.